2019
DOI: 10.3390/mps2020053
|View full text |Cite
|
Sign up to set email alerts
|

The DIVER Microscope for Imaging in Scattering Media

Abstract: We describe an advanced DIVER (Deep Imaging Via Emission Recovery) detection system for two-photon fluorescence microscopy that allows imaging in multiple scattering media, including biological tissues, up to a depth of a few mm with micron resolution. This detection system is more sensitive to low level light signals than conventional epi-detection used in two-photon fluorescence microscopes. The DIVER detector efficiently collects scattered emission photons from a wide area of turbid samples at almost any en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…One of the latest advancements includes implementation of frequency-domain FLIM in a multiphoton microscope capable of imaging deeper than conventional systems. 125 Finally, frequency-domain FLIM can be implemented without the use of costly pulsed lasers.…”
Section: Instrumentationmentioning
confidence: 99%
“…One of the latest advancements includes implementation of frequency-domain FLIM in a multiphoton microscope capable of imaging deeper than conventional systems. 125 Finally, frequency-domain FLIM can be implemented without the use of costly pulsed lasers.…”
Section: Instrumentationmentioning
confidence: 99%
“…Phasor-mapped FLIM and SHG images were acquired with an Olympus FVMPE-RS (Olympus, Waltham, MA) upright microscope equipped with an Insight X3 laser (Spectra-Physics, Santa Clara, CA) and a DIVER (Deep Imaging Via Enhanced Recovery) detector [ 36 , 37 ]. Samples were excited with a 740 nm laser in a two-photon excitation scheme at a laser repetition rate of 80 MHz.…”
Section: Methodsmentioning
confidence: 99%
“…64,65 By expanding this setup to multiphoton excitation on a microscope, phototoxicity of the sample is decreased and deeper penetration is possible for large tissue samples of up to 3 mm. 66 This technique can also be coupled with confocal imaging methods to measure cell morphological parameters or fluorescent markers of cell death. Walsh and Skala et al have shown that by measuring the optical redox index (OMI), a parameter that depends on the lifetime of NADH and FAD, they were able to see heterogeneous drug response within their human patient-and mousederived tumor organoids.…”
Section: What Assays Are Necessary To Interrogate This Complexity?mentioning
confidence: 99%
“…64,65 By expanding this setup to multiphoton excitation on a microscope, phototoxicity of the sample is decreased and deeper penetration is possible for large tissue samples of up to 3 mm. 66 This technique can also be coupled with confocal imaging methods to measure cell morphological parameters or fluorescent markers of cell death.…”
Section: Main Text/sectionsmentioning
confidence: 99%